Can biparietal diameter-to-femur length ratio be a useful sonographic marker for screening thanatophoric dysplasia since the first trimester? A literature review of case reports and a retrospective study based on 10,293 routine fetal biometry measurements - Liangcheng Wang; Yasushi Takai; Kazunori Baba; Yukiko Mikami; Masahiro Saito; Isao Horiuchi; Ryo Konno; Kenjiro Takagi; Hiroyuki Seki (Elsevier, 2017)
Objective: The aim of the study was to determine whether the biparietal diameter/femur length (BPD/FL) ratio can be used to detect thanatophoric dysplasia in the first trimester of pregnancy. Materials and Methods: Twenty-four reported cases of thanatophoric dysplasia diagnosed based on ultrasonographic results with molecular or radiographic diagnosis were included. All sonographic measurement records were extracted and reviewed, and the BPD/FL ratio was calculated for each gestational week. In addition, 10,293 routine fetal biometry measurements from 1395 cases of patients without skeletal dysplasia were compared. Results: The BPD/FL ratio in the control group decreased to less than 3 prior to gestational week 13, and to less than 2 prior to week 18. Of the 27 BPD/FL ratios obtained from 24 cases of thanatophoric dysplasia, none was in the control range. Conclusion: The BPD/FL ratio may be used to detect lethal skeletal dysplasias such as thanatophoric dysplasia since the first trimester.